Inverse psoriasis in a 6-month-old little girl. - Vicente-Ferreira, M.; Moreira, T.; Marques, A.R.; Maia, A.M.; Costa-Silva, M. (European Journal of Pediatric Dermatology, 2024)
Psoriasis is a chronic immune-mediated inflammatory skin disease with a recognized genetic predisposition and environmental triggers. Inverse psoriasis is a clinical variant of psoriasis that involves the intertriginous areas, including the inguinal, perineal, genital, intergluteal, axillary, or inframammary regions. This presentation is called “inverse” because it is the reverse of the typical presentation of plaque psoriasis on the extensor surfaces. It is sometimes difficult to diagnose because of its clinical similarity to other skin disorders involving the folds, including mainly mechanical intertrigo, fungal and bacterial infections, contact dermatitis, and seborrheic dermatitis.